Analisis Tafsir Misteri Kematian Musa dalam Ulangan 34: Apakah Musa Mati atau Diangkat? - Farudi Syukur; Christ Salamba Putra Pratama (Jurnal Budi Pekerti Agama Kristen dan Katolik, 2026)
The account of Moses’ death in Deuteronomy 34 has long drawn attention because of the questions it raises about what truly happened at the end of his life. The text leaves certain details unclear, especially regarding his burial and the absence of a known grave, which has led to different interpretations among scholars and faith communities. This study seeks to explore these interpretive possibilities, asking whether Moses simply died, was buried by God, or experienced a unique form of being taken by God. Using a qualitative approach based on literature review, this research engages biblical texts alongside selected contemporary studies. The discussion shows that the narrative intentionally allows room for multiple perspectives, rather than offering a single, definitive explanation. It also becomes clear that later Jewish and Christian traditions played a role in shaping how Moses’ death has been understood, often highlighting its deeper theological meaning. In the end, Moses’ death can be seen not only as the closing of his personal journey, but also as part of a larger story about leadership, transition, and God’s ongoing work among His people.